Greek-American Relations: A Critical Review - Couloumbis, Theodore A.; Iatrides, John O. (Modern Greek research series, 1980)
Keywords: Foreign relations; Greece; Greece; United States; award_winner; dept.psc; faculty_collection

Book Review: Protest movements in two indian states: A study of the gujarat and bihar movements . by ghanshyam shah. (delhi, india: ajanta publications, 1977. pp. xi + 171. 8.00.) - Rai, Kul B (American Political Science Review, 1980)
Keywords: book.review; dept.psc

Foreign aid and voting in the UN general assembly, 1967—1976 - Rai, Kul B (Journal of Peace Research, 1980)
This paper examines the relationship between foreign (economic) aid and the General Assembly votes for the period 1967-76. The countries included in this study are the United States, the Soviet Union, and those of their aid recipients which are considered less developed. Two related hypotheses, one on the use of aid as an inducement and the other as a reward or a punishment, are tested. The methods used are Index of Agreement, devised by Arend Lijphart, and Pearson's r. The findings indicate that the American aid is more effective as an inducement and the Soviet aid is more effective as a reward or a punishment. The former has a closer association with the General Assembly votes from 1967-73 than in later years. Economic aid is increasingly used by the United States more to serve its security interests in the Middle East than for any other purpose, and it is possible that not so much of a return for the American aid is expected in the UN as was the case earlier. © 1980, Sage Publications. All rights reserved.
Keywords: dept.psc